Pengaruh Seed Coating dengan Fungisida Benomil dan Tepung Curcuma terhadap Patogen Antraknosa Terbawa Benih dan Viabilitas Benih Cabai Besar (Capsicum annuum L.) - Heny Setiyowati; Memen Surahman; Suryo Wiyono (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2007)
The objective of this research was to study the effect of seed coating using Benomil and curcuma powder on seedborne diseases of antrachnose and seed viability of Capsicum annuum L.. This research was conducted in Laboratory of Plant Mycology and Laboratory of Seed Science and Technology IPB, from June to July 2006. This research consisted of three experiments, i.e.: (1) the effectiveness of seed coating in decreasing infection level of antrachnose fungus in the seed of chilli, (2) the effect of seed coating on seed viability, (3) the effect of seed coating in reducing infection level of antracnose at hypocotyl of chilli. The Experiment 1 and 3 used Randomized Complete Design and the experiment 2 used Randomized Complete Block Design. The result of this research showed that seed coating with Benomil and curcuma powder significantly decreased the infection level of antrachnose fungus on seed and hypocotyl (Benomil 2.5 g/l and curcuma powder 1 g/l). However, seed coating with curcuma 1 g/l had the lowest vigour index, seedling growth rate and seed germination (3%, 2.26%, 23%). Seedcoating with Benomil 2.5 g/l and curcuma powder did not significantly affect the maximum growth potential, seed germination, and vigour index. However, Benomil significantly decreased the seedling growth rate. Key wods : chilli, seed coating, antrachnose, curcuma, benomil, viability